Does Prior Performance Affect a Mutual Fund’s Choice of Risk? Theory and Further Empirical Evidence - Chen, Hsiu-lang; Pennacchi, George G. (Journal of Financial and Quantitative Analysis, 2009)
Abstract Recent empirical studies of mutual fund competition examine the relation between a fund’s performance, the fund manager’s compensation, and the fund manager’s choice of portfolio risk. This paper models a manager’s portfolio choice for compensation rules that can be either a concave, linear, or convex function of the fund’s performance relative to that of a benchmark. For particular compensation structures, a manager increases the fund’s “tracking error” volatility as its relative performance declines. However, declining performance does not necessarily lead the manager to raise the volatility of the fund’s return. The paper presents nonparametric and parametric tests of the relation between mutual fund performance and risk taking for more than 6,000 equity mutual funds over the 1962 to 2006 period. There is a tendency for mutual funds to increase the standard deviation of tracking errors, but not the standard deviation of returns, as their performance declines. This risk-shifting behavior appears more common for funds whose managers have longer tenures.